2023
DOI: 10.3389/fmolb.2023.1158912
|View full text |Cite
|
Sign up to set email alerts
|

In silico identification of modulators of J domain protein-Hsp70 interactions in Plasmodium falciparum: a drug repurposing strategy against malaria

Abstract: Plasmodium falciparum is a unicellular, intracellular protozoan parasite, and the causative agent of malaria in humans, a deadly vector borne infectious disease. A key phase of malaria pathology, is the invasion of human erythrocytes, resulting in drastic remodeling by exported parasite proteins, including molecular chaperones and co-chaperones. The survival of the parasite within the human host is mediated by P. falciparum heat shock protein 70s (PfHsp70s) and J domain proteins (PfJDPs), functioning as chaper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

3
0

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 73 publications
3
4
0
Order By: Relevance
“… 36 , 53 , 60 , 61 , 62 , 63 Furthermore, molecular docking studies have compared PfHSP70–PfHSP40 complexes to their human HSP70–HSP40 equivalents, and used these complexes to screen drug repurposing small molecule libraries to identify compounds with preferential binding to the malarial over the human system. 64 As expected, the J domain–NBD interfaces of PfHSP70-x–PFE0055c and human HSP70 (HSPA1A)-DNAJA1 both involved multiple topologically equivalent hydrogen bond interactions between highly conserved positively charged J domain helix II residues and NBD negatively charged residues ( Figure 2 ). 64 However, the interfaces were not identical, reflecting differences in the nature and number of contacts, with the malarial J domain–NBD interface containing a greater number of hydrogen bonds and an electrostatic energy of interaction that suggested a higher binding affinity.…”
Section: Malarial Hsps and Their Complexes As Drug Targetssupporting
confidence: 63%
See 4 more Smart Citations
“… 36 , 53 , 60 , 61 , 62 , 63 Furthermore, molecular docking studies have compared PfHSP70–PfHSP40 complexes to their human HSP70–HSP40 equivalents, and used these complexes to screen drug repurposing small molecule libraries to identify compounds with preferential binding to the malarial over the human system. 64 As expected, the J domain–NBD interfaces of PfHSP70-x–PFE0055c and human HSP70 (HSPA1A)-DNAJA1 both involved multiple topologically equivalent hydrogen bond interactions between highly conserved positively charged J domain helix II residues and NBD negatively charged residues ( Figure 2 ). 64 However, the interfaces were not identical, reflecting differences in the nature and number of contacts, with the malarial J domain–NBD interface containing a greater number of hydrogen bonds and an electrostatic energy of interaction that suggested a higher binding affinity.…”
Section: Malarial Hsps and Their Complexes As Drug Targetssupporting
confidence: 63%
“… 64 As expected, the J domain–NBD interfaces of PfHSP70-x–PFE0055c and human HSP70 (HSPA1A)-DNAJA1 both involved multiple topologically equivalent hydrogen bond interactions between highly conserved positively charged J domain helix II residues and NBD negatively charged residues ( Figure 2 ). 64 However, the interfaces were not identical, reflecting differences in the nature and number of contacts, with the malarial J domain–NBD interface containing a greater number of hydrogen bonds and an electrostatic energy of interaction that suggested a higher binding affinity. 64 Virtual screening studies identified five drug-like compounds that were potential preferential modulators of the malarial system: three binding at the interface of the PfHSP70–PfHSP40 complex (MBX 1641, PfHSP70-x–PFE0055c; and zoliflodacin and itraconazole, PfHSP70-2-PfSec63); and two binding to the J domain of the PfHSP40s (ezetimibe and a benzodiazepinone, PFE0055c J domain).…”
Section: Malarial Hsps and Their Complexes As Drug Targetssupporting
confidence: 63%
See 3 more Smart Citations